Long-term outcomes after fixation of pure chondral fragment from the femoral trochlea in adolescents –three case reports- - Shuto Yamashita; Ryohei Uchida; Tomohiko Matsuo; Norimasa Nakamura; Shuji Horibe; Yukiyoshi Toritsuka (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Purpose: Pure chondral fragments in adolescents are very rare, especially, fragments from the femoral trochlea. While satisfactory short-term outcomes after fixation were reported in several reports, long-term outcomes have still been unknown. Our objective is to evaluate the long-term outcomes after fixation for pure chondral fragment from the trochlea. Materials & Methods: Three adolescent patients (aged 13, 14, and 14 years) with pure chondral fragment from the trochlea underwent internal fixation using bio-absorbable pins at our institution. All patients were followed up for more than eight years. At final follow-up, all three patients were assessed by radiographs and magnetic resonance imaging (MRI) as well as clinical scores, including Lysholm questionnaires, and IKDC (International Knee Documentation Committee) score, KOOS (Knee injury and Osteoarthritis Outcome Score). Results: At final follow-up (12, 8, and 9 years postoperatively) all three patients were able to continue to play sports without any restriction. Radiographs showed no osteoarthritic changes and MRI showed good integration with the surrounding native cartilage and smooth surface in all cases. In all cases, Lysholm score and IKDC score were over 95, and most of KOOS were over 90. Conclusion: Fixation for pure chondral fragment from the femoral trochlea resulted in successful healing in adolescent patients with excellent radiographic and clinical outcomes in the long-term.